Palm Derived Products: A Bibliometric Analysis of Industrial Downstreaming - Judijanto, Loso (West Science Interdisciplinary Studies, 2025)
This study presents a comprehensive bibliometric analysis of global research on palm-derived products with a focus on industrial downstreaming. Using data extracted from the Scopus database and visualized through VOSviewer, the analysis maps the intellectual structure, thematic evolution, and collaborative patterns within the domain. Results reveal that "palm oil" is the most central keyword, with strong research clusters surrounding biodiesel, oleochemicals, biomass utilization, and emerging themes such as pyrolysis and biochar. Temporal analysis indicates a shift from conventional processing techniques to sustainability-driven innovations, particularly in waste valorization. Malaysia and Indonesia are identified as the leading contributors, with increasing global collaboration involving countries like China, India, the United States, and Nigeria. Co-authorship networks show concentrated but gradually integrating research communities. The study underscores the importance of interdisciplinary approaches, policy alignment, and sustainable industrial strategies in enhancing the economic and environmental impact of palm-based downstream industries. Recommendations for future research include focusing on life-cycle assessment, digitalization, and high-value derivative product development.